2020
DOI: 10.3389/fphys.2020.587358
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Programs Driving Shear Stress-Induced Differentiation of Kidney Proximal Tubule Cells in Culture

Abstract: Cultured cell models are an essential complement to dissecting kidney proximal tubule (PT) function in health and disease but do not fully recapitulate key features of this nephron segment. We recently determined that culture of opossum kidney (OK) cells under continuous orbital shear stress (OSS) significantly augments their morphological and functional resemblance to PTs in vivo. Here we used RNASeq to identify temporal transcriptional changes upon cell culture under static or shear stress conditions. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
3
17
0
1
Order By: Relevance
“…Subsequent studies demonstrated that growing OK cells under continuous shear stress and with increased O 2 availability dramatically improved their baseline endocytic capacity by roughly 5-fold compared with cells maintained under static conditions (Long et al 2017). In addition to increased expression of megalin and cubilin, cells cultured in this manner acquire morphological, transport, metabolic and transcriptional adaptations characteristic of PTs in vivo, including dense microvilli, greater sodium transport capacity, and oxidative metabolism (Long et al 2017;Ren et al 2019;Park et al 2020). Similar to the observations using cells cultured under static conditions and exposed acutely to flow, endocytic capacity in this more differentiated cell model is rapidly and reversibly regulated by changes in FSS (Long et al 2017).…”
Section: Endocytic Adaptation To Variations In Gfrsupporting
confidence: 63%
See 1 more Smart Citation
“…Subsequent studies demonstrated that growing OK cells under continuous shear stress and with increased O 2 availability dramatically improved their baseline endocytic capacity by roughly 5-fold compared with cells maintained under static conditions (Long et al 2017). In addition to increased expression of megalin and cubilin, cells cultured in this manner acquire morphological, transport, metabolic and transcriptional adaptations characteristic of PTs in vivo, including dense microvilli, greater sodium transport capacity, and oxidative metabolism (Long et al 2017;Ren et al 2019;Park et al 2020). Similar to the observations using cells cultured under static conditions and exposed acutely to flow, endocytic capacity in this more differentiated cell model is rapidly and reversibly regulated by changes in FSS (Long et al 2017).…”
Section: Endocytic Adaptation To Variations In Gfrsupporting
confidence: 63%
“…2019; Park et al . 2020). Similar to the observations using cells cultured under static conditions and exposed acutely to flow, endocytic capacity in this more differentiated cell model is rapidly and reversibly regulated by changes in FSS (Long et al .…”
Section: Endocytic Adaptation To Variations In Gfrmentioning
confidence: 99%
“…Opossum kidney cells (RRID:CVCL_0472; OK-P subclone originally obtained from M. Levi, Georgetown University) were cultured on transwell supports under continuous orbital shear stress as described in Long et al (2017). Cells grown in this manner harbour key features of PT cells in vivo, including a highly developed brush border and apical endocytic pathway, and high levels of megalin, cubilin and Dab2 expression (Long et al 2017;Park et al 2020;Ren et al 2020). Alexa Fluor-647 goat anti-rabbit immunoglobulin G (IgG) was purchased from Invitrogen (cat.…”
Section: Impact Of Igg and β 2 -Microglobulin On Albumin Uptakementioning
confidence: 99%
“…For example, we find only a small difference in Rab11a protein and mRNA expression between partially and fully differentiated OK cells, despite a dramatic elaboration of apical endocytic compartments and a five-fold enhancement in endocytic uptake in the latter. 3,4 In the absence of antibodies that recognize all species identically, we have found that droplet digital PCR provides a straightforward way to quantitatively compare transcript levels of proteins in different species, and demonstrate that megalin and cubilin transcripts in OK cells are expressed at levels comparable to those in mouse kidney cortex. 5 Although mRNA data do not necessarily translate to protein levels, the ratios of megalin to cubilin mRNA and protein expression in microdissected rat nephron PT segments correlate quite well.…”
mentioning
confidence: 96%
“…In OK cells at least, the enhanced oxygenation and mechanosensitive stimuli provided by culture in this way also cause expansion of the apical endocytic apparatus, development of basolateral membrane invaginations, and a shift to oxidative metabolism. 3,4 That said, studies in OK and LLC-PK1 cells are challenged by the lack of cross-reacting antibodies and genetic tools, and may not adequately replicate human disease models. Informed consideration of appropriate models for studies on PT function will improve both the effect and rigor of in vitro experiments that complement and extend studies performed in humans and animals.…”
mentioning
confidence: 99%